A Balanced Scorecard Execution: A Key to Success for A Sustainable Credit Union - Lianto Lianto (JURNAL TERAPAN MANAJEMEN DAN BISNIS, 2018)
The purpose of this essay is to explore and apply the wealth of the Balanced Scorecard framework in the management of credit unions. The effectiveness of this framework has contributed greatly to the business world. The cross functional paradigm in the Balanced Scorecard concept enables stakeholders to review various business activities in a holistic manner. A qualitative approach is used to explore concepts and their applications in business. This study offers a roadmap for credit unions to implement the Balanced Scorecard framework in the context of performance management.